Potential pharmacological mechanisms of four active compounds of Macleaya cordata extract against enteritis based on network pharmacology and molecular docking technology - Yang, Pingrui; Zhong, Chonghua; Huang, Huan; Li, Xifeng; Du, Lin; Zhang, Lifang; Bi, Shicheng; Du, Hongxu; Ma, Qi; Cao, Liting (Frontiers in Physiology, 2023)
Background: Macleaya cordata extract (MCE) is effective in the treatment of enteritis, but its mechanism has not been fully clarified. Therefore, this study combined network pharmacology and molecular docking technologies to investigate the potential pharmacological mechanism of MCE in the treatment of enteritis. Methods: The information of active compounds in MCE was accessed through the literature. And the databases of PubChem, PharmMapper, UniProt, and GeneCards were used to analyze the targets of MCE and enteritis. The intersection of drug and disease targets was imported into the STRING database, and the analysis results were imported into the Cytoscape 3.7.1 software to construct a protein-protein interaction (PPI) network and to screen core targets. Metascape Database was conducted for Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. The Autodock Tools software was used for the molecular docking of the active compounds with the core targets. Results: MCE has four active compounds, namely, sanguinarine, chelerythrine, protopine, and allocryptopine, and a total of 269 targets after de-duplication. Furthermore, a total of 1,237 targets were associated with enteritis, 70 of which were obtained by aiding the drug-disease intersection with the aforementioned four active compound targets of MCE. Five core targets including Mitogen-Activated Protein Kinase 1 and AKT Serine/Threonine Kinase 1 were obtained using the PPI network, which are considered as the potential targets for the four active compounds of MCE in the treatment of enteritis. The GO enrichment analysis involved 749 biological processes, 47 cellular components, and 64 molecular functions. The KEGG pathway enrichment analysis revealed 142 pathways involved in the treatment of enteritis by the four active compounds of MCE, among which PI3K-Akt and MAPK signaling pathways were the most important pathways. The results of molecular docking showed that the four active compounds demonstrated good binding properties at the five core targets. Conclusion: Pharmacological effects of the four active compounds of MCE in the treatment of enteritis involve acting on signaling pathways such as PI3K-Akt and MAPK through the key targets such as AKT1 and MAPK1, thus providing new indications for further research to verify its mechanism.